Combined intracavitary and interstitial brachytherapy of cervical cancer using the novel hybrid applicator Venezia: Clinical feasibility and initial results - Walter, Franziska; Maihöfer, Cornelius; Schüttrumpf, Lars; Well, Justus; Burges, Alexander; Ertl-Wagner, Birgit; Mahner, Sven; Belka, Claus; Gallwas, Julia; Corradini, Stefanie (Brachytherapy, 2018)
Purpose: To report on first-in-human experience and the initial clinical results using the hybrid applicator Venezia (Elekta, Sweden) in the treatment of patients with locally advanced cervical cancer. Material and Methods: Between March, 2017, and February, 2018, a total of 40 fractions were performed on patients undergoing definitive chemoradiation and brachytherapy (BT) for cervical cancer. A plan comparison was conducted evaluating the hybrid applicator with the clinically used intracavitary and interstitial (IC/IS) BT against a standard plan prescribed to Point A and a manually optimized plan using only intracavitary (IC) BT. Overall 80 treatment plans were retrospectively generated. Results: The clinical use of the hybrid applicator system proved to be feasible in all 40 treatment fractions. The applicator consists of the IC tandem and two lunar-shaped ovoids forming a ring that serves as a template for defined parallel and oblique (12°) needle insertion. MRI preplanning was performed the day before the implant. One to six needles were placed per fraction, and overall a total of 66 needles were used. No complications such as bleeding or organ penetration occurred due to needle placement. Significant differences in IC/IS, Point A, and IC plans were derived for dose application to the target volume; D 90 high-risk clinical target volume was 90.7 vs. 88.1 vs. 80.8 Gy (p = 0.008). Likewise, sparing of organs at risk differed significantly for bladder D 2cc 79.4 vs. 91.8 vs. 79.2 Gy (p = 0.03) and rectum D 2cc 58.7 vs. 67.3 vs. 62.5 Gy (p = 0.03). Conclusion: The clinical application of the Venezia applicator is feasible and allows significantly improved dose coverage while at the same time sufficiently sparing organs at risk.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Cervical cancer; Combined intracavitary/interstitial brachytherapy; Hybrid applicator; MR-guided brachytherapy